Engaging Novice Writers in Online Collaborative Review through Peer-Review Circles - Nur, Sahril; Anas, Ismail; Rahayu, Rahayu (Universitas Negeri Makassar, 2022)
In response to the Covid-19 pandemic, this article presents online Peer-Review Circles (PRC) as an innovative and collaborative approach to academic writing, mainly proofreading and copy-editing processes. It aims to engage novice second language (L2) writers in online joint review and increase their understanding of pre-reviewing scholarly papers before submission. The authors had observed that a large number of doctoral students are still considered novice writers. Therefore, there was a need for a practical approach to improve their review skills and engage them in online PRC activities. Grounded in Monologue-Dialogue-Discussion (MDD) Circles (Manning & Jobbitt, 2018), this article extends its potential to be adopted and used beyond the classroom and mandatory ELT contexts. MDD requires three consecutive stages: 1) primary reviewer’s monologue, 2) primary and secondary reviewer’s dialogue, and 3) writer and the reviewers perform a group discussion. These activities will help the writers to look after the manuscripts simultaneously from a PRC perspective. We also developed peer review Feedback Questions (FQs) to guide the reviewers to perform meaningful discussions. The output of the PRCs will likely be an initial review or a pre-evaluation process to improve the manuscript quality, readability, and publishability.